IMPLEMENTASI PERDA NOMOR 6 TAHUN 2011 TENTANG PAJAK REKLAME DI KOTA SEMARANG - Rahmat Tri Febriyanto; Ari Subowo (Journal of Public Policy and Management Review, 2016)
Advertisement tax is a levies that local districts / cities on the implementation of the billboard. Advertising Tax convening aims to help improve the original income in order to carry out the development and care of the household own areas. In fact in the implementation of policy implementation have not been fully able to bring results in line with the target set. The focus of this research is the Implementation Regulations of Law 6 of 2011 about the advertisement tax in Semarang as the locus of research. This study uses theory implementation proposed by George Edward III, Meter and Horn theory and the theory of Grindle. This type of research is explanatory research that examines the influence between variables with hypothesis testing. The unit of analysis is the implementing agency personnel policy the implementation Regulations of Law 6 of 2011 about the advertisement tax in Semarang related (Employee field of local taxes). A representative sample use Proportional Random Sampling technique by taking 30 respondents. Statistical testing to measure the accuracy of instruments questions using validity and reliability test. hypothesis testing using the formula Kendall Rank Correlation Coefficient with Z Significance Tests with SPSS method and coefficient of determination.. The research proves that there is a positive and significant relationship between attitudes to the implementation Regulations of Law 6 of 2011 about the advertisement tax in Semarang by 11.4% relationship. There is a positive and significant relationship between communication with the implementation Regulations of Law 6 of 2011 about the advertisement tax in Semarang by 16.4% relationship. These results indicate that the hypothesis proposed in this study received. Based on the research, in order to achieve the successful Implementation Regulation 6 of 2011 about the advertisement tax, DPKAD Semarang need to conduct more intensive training to officers and providing extension or a more intensive socialization to taxpayers.